2021
DOI: 10.1088/1742-6596/1845/1/012056
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Fuzzy Logic as a Control and Monitor of Oil Quality Using Android

Abstract: Viscosity oil index becomes the prominent indicator in the process of engine generator set lubrication. This simulation design used to inform the oil quality and switch off the generator set when the oil quality is not moderate. DC motor rotation and rotary encoder utilize as controller of oil viscosity. Optocoupler sensor is an RPM controller, LDR light sensor is an oil brightness indicator. DS18B20 sensor is the indicator of temperature when the oil work is at low state 0°C-30°C, normal 30°C-50°C and overhea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…According to literature survey, absorption peaks are observed near wave numbers 970 cm − 1 and 860 cm − 1 . These numbers have a Previous research showed the possibility of using colour features to analyse particles for automated wear debris classi cation (Myshkin et al, 2001).Published literature shows use of an optical colour sensor with a blue LED as a light source and LDR or colour scale as per the ASTM D1500 standard for colour analysis (Suhanto et al, 2021). That displays a strong correlation to a change in voltage across LDR with the pH value and the viscosity of the oil (Kumar et al, 2005).The RGB sensor output in three wavelengths viz.…”
Section: Introductionmentioning
confidence: 99%
“…According to literature survey, absorption peaks are observed near wave numbers 970 cm − 1 and 860 cm − 1 . These numbers have a Previous research showed the possibility of using colour features to analyse particles for automated wear debris classi cation (Myshkin et al, 2001).Published literature shows use of an optical colour sensor with a blue LED as a light source and LDR or colour scale as per the ASTM D1500 standard for colour analysis (Suhanto et al, 2021). That displays a strong correlation to a change in voltage across LDR with the pH value and the viscosity of the oil (Kumar et al, 2005).The RGB sensor output in three wavelengths viz.…”
Section: Introductionmentioning
confidence: 99%